Bacillus Calmette-Guerin (BCG) as an Intralesional Therapy for Cutaneous Metastatic Malignant Melanoma: A Literature Review - Dina, Farisa B; Kurnia, Ahmad (UI Scholars Hub, 2024)
Introduction. Malignant melanoma is the most lethal form of skin cancer and is the third most common cause of death of all malignancies in the world. Cutaneous metastatic lesions are the earliest and the most frequently encountered metastatic lesions in malignant melanoma. The use of Bacillus Calmette-Guerin (BCG) as an intradermal therapy agent has been long debated due to its effectiveness and adverse effects. This literature review aims to provide a comprehensive explanation regarding the use of intralesional BCG in establishing local control and preventing recurrence in cutaneous metastatic malignant melanoma. Method. A literature search was conducted on various online databases. The articles that were obtained were selected according to the 2020 PRISMA flow diagram. Among 79 articles obtained, six selected articles were included in this study. Results. Five included studies stated that intralesional BCG effectively induces complete regression of cutaneous metastatic lesions of malignant melanoma. Variable results have been obtained regarding the effectiveness of intralesional BCG in preventing the recurrence of malignant melanoma. In three studies, significant differences were found in disease-free and median survival, but no studies included incidence of recurrence data in their results. Conclusion. BCG can be considered as an intralesional therapy agent of choice to induce local control in cutaneous metastatic malignant melanoma. However, its use has proven ineffective in preventing cutaneous metastatic malignant melanoma recurrence.